PANDANGAN INVESTOR TERHADAP EMAS SEBAGAI INVESTASI SEJAK 2012 - Felisia .; Felisca Oriana Surjoko (Center for Economic Studies Universitas Katolik Parahyangan, 2013)
We invest to improve our welfare, which for our purposes can be defined as monetary wealth, both current and future. Investors also seek to manage their wealth effectively, obtaining the most from it while protecting it from inflation, taxes, and other factors. Gold is one type of investments. Gold is considered as priceless asset in the world. It has limited supplies because of scarce resource. There are some reasons why people interested in investing gold, such as its value of liquidity, protection, portability, durability, ownership and stewardship, low risk level, and also free of tax expense. Since 2012, gold price is becoming decreased. According to some information, global inflation has great influence to this situation. Safe haven status of gold is now being questioned by gold investors.